A Typical Presentation of Trigeminal Neuralgia Induced by Intracranial Hypertension Mimicking Sinusitis - MD, Pulwasha Maria Iftikhar; MBBS, Maham Munawar; MD, Mohammed Ali Pour; MBBS, Saad Nasir; MD, Arslan Inayat (Archives of Clinical and Medical Case Reports, 2020)
Trigeminal neuralgia is a chronic pain syndrome that affects the trigeminal nerve. Trigeminal neuralgia is broadly classified into two major subtypes as typical and atypical trigeminal neuralgia. The former is described as repetitive attacks of sharp, severe, excruciating pain with pain-free intervals while the latter is characterized by dull burning facial pain. Facial pain is the main feature of the trigeminal neuralgia but it could be the symptoms of multiple sinogenic and non-sinogenic disorders, it is difficult to distinguish sinogenic pain caused due to sinusitis from non-sinogenic facial pain caused by other etiologies such as trigeminal neuralgia, migraine and idiopathic intracranial hypertension to avoid imprecise treatment at early stages and for a better prognosis. Here, we present the case of a 56-years-old woman, who presented with trigeminal neuralgia mimicking chronic sinusitis. Delayed diagnosis can result in a poor quality of life, unnecessary intervention, and financial burden.